Ján Kollár avagy a szláv nemzet jó tulajdonságai? - Kiss Szemán, Róbert (Slavia Centralis, 2020)
Jan Kollar or good characteristics of Slavic nationsThis study calls attention to Kollár’s two-part sermon which exerted a large influence on the national consciousness of the modern Slav nations. Kollár discusses five good qualities of the Slav nation: its godliness, diligence, cheerfulness, love of mother tongue, and forbearance towards other nations. Among the possible prototypes of this sermon are a paper by János Horváth, entitled "On the Religious and Moral Condition of the Hungarians" in the 1817 volume of Tudományos Gyűjtemény. The manner of adoption can be seen as creative artistic activity, in the course of which Kollár significantly reinterpreted the qualities in question and applied them to the Slav nation.
Keywords: National consciousness of the Slav nations; history in the Romantic Age; romantic version of the; sermon in the 19th century; modern national identity; Hungarian and Czech/ Slovak literature in the 19th century